2014
DOI: 10.1007/s00203-014-1005-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival, prophage induction, and invasive properties of lysogenic Salmonella Typhimurium exposed to simulated gastrointestinal conditions

Abstract: This study was designed to evaluate the viability, prophage induction, invasive ability, and relative gene expression in lysogenic Salmonella Typhimurium exposed to the simulated gastric juice (SGJ) at pH 2 (SGJ-2), 3 (SGJ-3), 4 (SGJ-4), and 5 (SGJ-5) for 30 min followed by 0.5 % bile salts for 2 h. The susceptibility of lysogenic S. Typhimurium increased with decreasing pH value and increasing bile salt concentration. The lysogenic S. Typhimurium cells were least susceptible to SGJ-4 and SGJ-5, showing <1 log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…To increase virion titers and search for inducing signals, A2-165 F. prausnitzii cultures were treated with different concentrations of three potent inducers of phage lytic cycle: mitomycin C, hydrogen peroxide, and bile salts (cholate/deoxycholate [1:1]) [ 13 , 42 ]. Mitomycin C in particular causes DNA damage, which is a general signal for prophage derepression.…”
Section: Resultsmentioning
confidence: 99%
“…To increase virion titers and search for inducing signals, A2-165 F. prausnitzii cultures were treated with different concentrations of three potent inducers of phage lytic cycle: mitomycin C, hydrogen peroxide, and bile salts (cholate/deoxycholate [1:1]) [ 13 , 42 ]. Mitomycin C in particular causes DNA damage, which is a general signal for prophage derepression.…”
Section: Resultsmentioning
confidence: 99%
“…Since then many more prophages have been identified, every time a set of new Salmonella genomes is sequenced. Dormant prophages are transmitted vertically along with bacterial cell division and can be induced under stressful conditions, such as DNA damages or in animal guts (Kim et al ., ). They can also undergo spontaneous induction, which can increase the fitness of a given strain whenever in competition when entering a new niche (Bossi et al, ).…”
Section: Prophage Abundance and Integration Sites In S Enterica Genomesmentioning
confidence: 97%
“…8C), suggesting that BBR-induced alterations in the gut microbiome observed in complex consortia may be partly due to induction of the phage lytic cycle through bile acid toxicity. Indeed, previous studies have shown that bile acids induce phage lytic cycle in intestinal pathogens [35,36].…”
Section: Discussionmentioning
confidence: 99%